Experimental investigation of a thermoelectric generator - Siau, Meng Xiong. (2012)
Thermoelectric power generation converts heat into electrical power. The thermoelectric effect was discovered back in the 1800s but has only gained significant interest in recent years due to technological advancements in the semiconductor industry and the need to find renewable sources of energy due to depleting fossil fuels. Despite this, thermoelectric power generators are not commercially viable due to the low efficiencies (electrical power output over heat input) of the materials.